Equine keratomycosis in Japan. (28th February 2012) - Wada, Shinya; Hobo, Seiji; Ode, Hirotaka; Niwa, Hidekazu; Moriyama, Hidekazu
Abstract Objective To describe the incidence, clinical progress, visual outcome, and laboratory findings of equine keratomycosis in Japan. Procedure Retrospective study of the medical records of horses clinically and mycologically diagnosed with keratomycosis at the Equine Hospitals of the Japan Racing Association from 2005 to 2011. Results The diagnosis of keratomycosis was confirmed in eight horses (40.0% of the 20 horses with infectious keratitis from which fungi and/or bacteria were isolated). Fungi recovered from corneal swabs were identified as Aspergillus flavus (4), Aspergillus niger (1), Fusarium solani (1), and Mortierella wolfii (2). All horses were treated medically with topical antifungals, and one horse was also treated surgically. The median of treatment period was 40 days. Two horses were rendered blind in the affected eye and the others retained vision. Conclusions Equine keratomycosis comprises a considerable portion of infectious keratitis in Japan, and the causative fungi that we isolated had been isolated previously from horses with keratomycosis in other regions with the exception of M. wolfii. Culture and cytological examination of corneal lesions should be immediately performed on eyes with signs of keratitis, particularly on those not improving with antibacterial medication, as early initiation of aggressive antifungal treatment tended to result in better outcome and shorter treatment period.